Catastrophic Cardiac Amyloidosis. (4th November 2010) - Panduranga, Prashanth; Mukhaini, Mohammed
Abstract : We report a case of a 61-year-old patient presenting with cardiogenic shock. His echocardiogram suggested typical features of cardiac amyloidosis. This case demonstrates that cardiac amyloidosis can present acutely and may be catastrophic.